PENGARUH FASHION TERHADAP PERUBAHAN GAYA BERPAKAIAN MAHASISWA JURUSAN ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL UINSU STAMBUK 2019 - Hadi, Ridwan; Ritonga, Muhammad Husni (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This research aims to find out how influential fashion is on changes in the dress style of students of the Communication Sciences study program, Faculty of Social Sciences, Uinsu class of 19. The type of research used is quantitative research by distributing questionnaires to students of Communication science class of 19. The results showed that fashion had an effect on changes in the style of dress of students in the Communication Science study program, Faculty of Social Sciences, Uinsu class of 19 by 77.5% and the remaining 22.5% was influenced by other factors or it could also be said to have no effect.